Unlocking PGPR-Mediated Abiotic Stress Tolerance: What Lies Beneath - Mellidou, Ifigeneia; Karamanoli, Katerina (Frontiers in Sustainable Food Systems, 2022)
In the forthcoming era of climate change and ecosystem degradation, fostering the use of beneficial microbiota in agroecosystems represents a major challenge towards sustainability. Some plant-associated bacteria, called Plant Growth Promoting Rhizobacteria (PGPR), may confer growth-promoting advantages to the plant host, through enhancing nutrient uptake, altering hormone homeostasis, and/or improving tolerance to abiotic stress factors and phytopathogens. In this regard, exploring the key ecological and evolutionary interactions between plants and their microbiomes is perquisite to develop innovative approaches and novel natural products that will complement conventional farming techniques. Recently, details of the molecular aspects of PGPR-mediated tolerance to various stress factors have come to light. At the same time the integration of the recent advances in the field of plant-microbiome crosstalk with novel -omic approaches will soon allow us to develop a holistic approach to ‘prime’ plants against unfavorable environments. This mini review highlights the current state of the art on seed biopriming, focusing on the identification and application of novel PGPR in cultivated plant species under conditions where crop productivity is limited. The potential challenges of commercializing these PGPR as biostimulants to improve crop production under multiple environmental constraints of plant growth, as well as concerns about PGPR application and their impact on ecosystems, are also discussed.